The Pre-Colonial Boundary as a Post-Colonial Problem: A Historical and Legal Analysis of the Nigeria-Cameroon Border - Ibiang Okoi (Pinisi Journal of Social Science, 2026)
The Nigeria-Cameroon border, running from the Gulf of Guinea to Lake Chad, remains one of Africa’s most contested international boundaries. This paper argues that the post-colonial problems along this border stem directly from the imposition of colonial boundaries that disregarded pre-existing African political and ethnic configurations. Drawing on archival records, international legal decisions, and contemporary ethnographic studies, the paper first reconstructs the nature of pre-colonial boundaries in the region, emphasizing their fluidity, negotiability, and cultural embeddedness. It then traces the colonial construction of the boundary through the Anglo-German agreements of 1893, 1913, and the subsequent League of Nations mandate system. The core of the paper demonstrates how the post-colonial adoption of the principle of uti possidetis juris transformed artificially drawn colonial lines into permanent international borders, generating three interlocking problems: the fragmentation of ethnic groups (notably the Ejagham, Boki, and Ijaw), the militarization of borderland communities, and resource conflicts exemplified by the Bakassi Peninsula dispute. The 2002 International Court of Justice ruling and the 2006 Greentree Agreement are analyzed as incomplete solutions that reaffirmed colonial boundaries without addressing pre-colonial realities. The paper concludes that while colonial boundaries are legally fixed, sustainable peace requires recognizing pre-existing transborder networks and implementing people-centred border management.